The functioning of homonym and polysemy in the Arabic term system - Mustafayeva, А. А. (Journal of Oriental Studies, 2016)
The paper shows the processes of homonym and polysemy based on the Arabic terminology. In spite of the aim of a term to have one meaning, there are some processes of polymeaning in the terminological systems